PCSK9-D374Y Suppresses Hepatocyte Migration through Downregulating Free Cholesterol Efflux Rate and Activity of Extracellular Signal-Regulated Kinase - Lei Huang; Ying Cheng; Yulian Mu; Kui Li (Analytical Cellular Pathology)
Proprotein convertase subtilisin/kexin type 9 can mediate the intracellular lysosomal degradation of the low-density lipoprotein receptor protein in hepatocytes and decrease the liver’s ability to scavenge low-density lipoprotein cholesterol from circulation, resulting in high levels of cholesterol in the circulatory system. Current studies have primarily focused on the relationship between PCSK9 and blood lipid metabolism; however, the biological function of PCSK9 in hepatocytes is rarely addressed. In this study, we evaluate its effects in the human hepatoma carcinoma cell line HepG2, including proliferation, migration, and free cholesterol transport. PCSK9-D374Y is a gain-of-function mutation that does not affect proliferation but significantly suppresses the migration and cholesterol efflux capacity of these cells. The suppression of the transmembrane outflow of intracellular-free cholesterol regulates small G proteins and the suppression of extracellular signal-regulated kinase. In summary, PCSK9-D374Y affects hepatocyte features, including their migration and free cholesterol transport capabilities.